2020
DOI: 10.2166/wst.2020.312
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant extracts on growth and photosynthetic fluorescence characteristics of Microcystis flos-aquae

Abstract: Abstract The cyanobacteria Microcystis flos-aquae can cause harmful algal blooms in waterbodies, which threaten the normal functioning of aquatic ecosystems and human health. The plant extracts are considered as the promising algaecides. In this study, the effects of ten plant extracts (Cinnamomum camphora, Ginkgo biloba, Firmiana platanifolia, Salix babylonica, Euphorbia humifusa, Erigeron annuus, Solidago canadensis, Alternanthera philoxeroides, Thalia dealbata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In liquid medium, methanolic extracts of the four plant species possess statistically signi cant algaecidal activity against the toxic cyanobacterium M. aeruginosa. These results are similar to values obtained in some works such as that of Shi et al 2020, where they analyzed the effects of ten plant species on the growth of Microcystis os-aquae, reporting that all species showed signi cant inhibitory effects, with Alternanthera philoxeroides showing the highest degree of inhibition (77.30%), after 4 days of exposure to a concentration of 3 g/L. In another study published by Tazart et al, 2018, they observed that, aqueous extracts of Ranunculus aquatilis and Nasturtium o cinale showed inhibitions of 100 and 75% in M. aeruginosa positively correlating the polyphenols, avonoids and total tannins levels and the degree of inhibition of these species, similar to what was observed in our research with extracts of A. mexicana, B. spectabilis and L. tridentata.…”
Section: Discussionsupporting
confidence: 92%
“…In liquid medium, methanolic extracts of the four plant species possess statistically signi cant algaecidal activity against the toxic cyanobacterium M. aeruginosa. These results are similar to values obtained in some works such as that of Shi et al 2020, where they analyzed the effects of ten plant species on the growth of Microcystis os-aquae, reporting that all species showed signi cant inhibitory effects, with Alternanthera philoxeroides showing the highest degree of inhibition (77.30%), after 4 days of exposure to a concentration of 3 g/L. In another study published by Tazart et al, 2018, they observed that, aqueous extracts of Ranunculus aquatilis and Nasturtium o cinale showed inhibitions of 100 and 75% in M. aeruginosa positively correlating the polyphenols, avonoids and total tannins levels and the degree of inhibition of these species, similar to what was observed in our research with extracts of A. mexicana, B. spectabilis and L. tridentata.…”
Section: Discussionsupporting
confidence: 92%